Group Social Potential: Concept, Main Features and Components (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The levels of social potential, including: nano-, micro-, macro- and metalevel and its carrier are certain in the article. In research attention is concentrated on the study of group social potential, that is formed on a nanolevel and it carriers are families, certain groups, associations, community.Based on generalization and systematization of works of scientists and results of previous researches of author, it was succeeded to distinguish the signs of group social potential and basis of it to give own vision of the essence of this concept as possibilities of group of people to act and achieve a joint purpose, that is formed in the process of socialization and establishment of stable social relations and focused on appropriation of resources and their further effective use with the purpose of obtaining a synergistic effect. The component structure of group social potential are offered and types considering the formed criteria are selected.
Keywords: social potential, group social potential, group, collective, human potential, reproductive potential, communicative potential, organizational potential.